EFFECTS OF PLASTIC STRAW MANIPULATIVES ON ELEMENTARY MATH ADDITION SKILLS - Eka Ramiati; Imam Mashuri; Riza Faishol; Dewi Wariyani; Yuli Tri Andini; Ellyana Ilsan Eka Putri (PGMI Department of Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
This study examines the impact of using plastic straws as concrete manipulatives on first-grade students' addition skills in mathematics at MI An-Nidhom, a rural Islamic elementary school in Indonesia. Addressing the challenge of teaching abstract mathematical concepts to young learners, the research explores an innovative, low-cost, and sustainable pedagogical approach. Employing a mixed-methods design with a one-group pretest-posttest model (N=34), the study measured learning outcomes through standardized tests, classroom observations, and teacher interviews. Results demonstrated significant improvement in mathematical proficiency (t(33)=11.109, p<0.001, d=1.89), with 82% of students successfully transitioning from concrete to abstract understanding. The intervention also yielded environmental benefits, reducing plastic waste by 72% while enhancing students' ecological awareness. These findings contribute to both educational practice and sustainable development goals by demonstrating how locally available materials can effectively support foundational numeracy skills in resource-limited settings.